Gold-catalysis: highly efficient and regio-selective carbonyl migration in alkynyl-substituted indole-3-carboxamides leading to azepino[3,4-b]indol-1-ones - Hashmi, A. Stephen K.; Yang, Weibo; Rominger, Frank (Advanced synthesis & catalysis, 2012)
An unprecedented rearrangement/anellation sequence allows the clean synthesis of azepino[3,4-b]indol-1-ones from readily available starting materials. Alkyne-substituted indole-3-carboxamides were prepared and converted to azepino[3,4-b]indol-1-ones by the SPhosAuNTf2 catalyst (SPhos=2-dicyclohexylphosphino-2′,6′-dimethoxybiphenyl). The new connectivity, which involves an unprecedented 3,2-shift of an acylamino group for the product formation, was proven by a crystal structure analysis.